Reevaluation of Land Suitability for Soybean Plants in North Sumatra, Indonesia - Handayani, Leni; Mazlina, Mazlina; Riyanti, Riyanti; Ilvira, Rika Fitri; Siregar, Rahma Sari (Universitas Panji Sakti, 2025)
This study was designed to reevaluate the adjustment of land suitability classes. This study was conducted in North Sumatra Province, precisely in 4 regencies, namely Simalungun, Langkat, Deli Serdang, and Serdang Bedagai Regencies. The study used land suitability classes. Related to rooting media and nutrient retention parameters, the results of a semi-detailed land suitability study for soybean plants in Deli Serdang, Serdang Bedagai, and Langkat Regencies showed that the land was only marginally suitable (S3 rc, nr). In Simalungun Regency, efforts were made to increase the suitability of potential land to a marginally suitable class with the rooting media factor (S3 rc) and the water availability and nutrient retention factor (S3 wa, nr). This was done by attempting to increase the adaptability of potential land to a marginal suitability class with a water availability factor (S3 wa). The land suitability class in the research area for soybean plants includes the marginal suitability class (S3), so planting soybean commodities results in less than maximum production with limiting factors of rainfall and nutrition retention. To improve nutrient retention by adding organic materials, the limiting factor of rainfall is relatively high by creating drainage channels.